KVADRAT TEŃLEMEGE KELTIRIW ARQALI SHESHILETUǴIN QURAMALI ALGEBRALIQ TEŃLEMELERDI SHESHIW USILLARI - Djumabaev, N. (SCIENCE and SOCIETY, 2023)
This article provides methods for solving complex equations by reduction to quadratic equations.